Certified Teacher Performance: Principal Leadership Organizational Culture Rewards and Work Motivation - Dody Yogaswara; Candra Wijaya; Saiful Akhyar Lubis (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study aims to analyze the causal relationship between the leadership of madrasah heads, organizational culture, and the provision of rewards on the work motivation and performance of certified teachers in Madrasah Ibtidaiyah Negeri (MIN) in Bireuen Regency. In particular, it seeks to uncover both the direct and indirect effects of these organizational factors on teacher performance through the mediating role of work motivation. Methodology: The research adopts an ex post facto design and employs exploratory quantitative analysis. A sample of 242 certified teachers was selected using random sampling, with a significance level of 0.05. Data were analyzed using path analysis to identify the magnitude and direction of influence among the variables. Main Findings: The findings reveal that the leadership of the madrasah head, organizational culture, and the provision of rewards each have a significant total effect both directly and indirectly on teacher performance. Leadership influences performance through motivational pathways, while organizational culture and reward systems serve as structural supports that reinforce professional commitment and productivity. Novelty/Originality of this Study: Unlike previous studies that often isolate one or two variables, this research presents a comprehensive and integrative model that simultaneously evaluates multiple external (leadership, culture, rewards) and internal (motivation) factors. Conducted in a unique institutional and geographic context public Islamic elementary schools in Bireuen Regency this study contributes novel empirical evidence relevant to performance improvement strategies in faith-based educational environments, especially in the post-certification era of Indonesian teacher reform.